Investigating factors influencing the purchase decision of properties in Kubang Pasu by local buyers - Ab Ghani, Nur Syazwani; Goh, Tian Yeow; Hassan, Hasmawati; Goo, Wei How; Hussin, Suriza Masdura; Basir, Nurtiara; Osman, Nor Hasni (2015)
Affordability of local buyers, renovation and design of the houses and implementation of Government Service Tax (GST) are directly affecting the price of the houses locally. At the same time, housing developers have to explicitly balance between cost and quality of the houses.In view of that, this paper aims to investigate importance factors involved in purchase decision on properties in the future residential projects in Kubang Pasu.This research proceeds into identifying how price and quality influenced the purchase decision of properties by local buyer.Besides using a survey to gather respondents' perceptions, this research also employs key perspectives of relevant stakeholders into the analysis. It is expected that the findings could contribute towards greater understanding in view of housing industry.It is also expected to provide good insights on managerial applications.